(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1994)
A simple way to get accurate figures of the outline of cephalopod shells is hereunder described. It consists in photocopying carefully sectioned casts made of plaster. The usefulness of the method is evaluated in comparisons with the other available techniques.